Radio Sensitization of Farmers towards the Production of Genetically Modified Foods (GMFs) in Lokoja, Nigeria - Mbazu, C. Emmanuel; Oladokun, D. Bolaji; Mohammed, D. James; Unwuchola, A. Anderson; Babatunde, O. Emmanuel (Covenant Journal of Communication, 2024)
It is no gainsaying that radio bridges the gap between the rural dwellers and the city dwellers in every society. It also acts as an intermediary between development facilitators and the beneficiaries, especially in the area of agriculture. However, it appears that no study has been conducted to investigate the level of farmers’ sensitization on radio towards the production of genetically modified foods in Lokoja, hence this present study assesses radio sensitization of farmers towards the production of genetically modified foods in Lokoja, Nigeria. It assessed the level of exposure of farmers to GMF programmes on radio in Kogi State. The study is anchored on the Media Dependency Theory and Elaborative Likelihood Model. Survey research design was employed. Three hundred and eighty copies of questionnaire were distributed, retrieved and analysed. Multistage sampling technique was employed. Instruments used were questionnaire and interview guide. It was found out that farmers in Lokoja of Kogi State are exposed to information on Genetically Modified Foods on radio through Grace FM agricultural programme. They considered such information as not comprehensive enough, even though they attested becoming aware of GMFs via the programme. The study recommends that agricultural stakeholders should harness the potency of radio to inform, educate and enlighten farmers about new ideas as it relates to all areas of agriculture.